A Critical Review on Sthoulya Roga. - gupta, Piyush; mathur, Julee; Sandeep (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda being an age-old life science is as scientific and proves to be useful even in this age of 21stcentury. It provides a holistic approach to our daily life be it physical or mental health. According to Ayurveda Sthoulya roga has also been describe as life style diseases which occurs if a person does not follow dinacharya, ritu-chararyapathya and apathya as mentioned in Ayurvedic texts. Charak samhitais one of the renowned samhita of ayurveda which quoted sthoulya under the eight varieties of impediments designated as astaunindita purusha, atisthoulya comprise one of them. Charak has also mentioned it as a santarpanjanita roga which leads to eight defects under lying i.e., Sthoulyapurusha, Ayuharsa, Javoparodha, Alpaovyavayita, Daurbalya, Daurgandhya, Swedabadha, Ati-trisha, Ati-kshudha. Dalhana mentioned sthuolya in medoroga. He specified mandaagni and dhatvagnimanda involved in pathogenesis of the disease. But No separate disease in the name of Sthoulya is described in various texts of ayurveda. In this article we are making effort to collect matter of sthoulya scattered in various ayurvedic texts.